Perencanaan Jaringan Pipa Pembawa Untuk Memenuhi Kebutuhan Air Bersih Desa Purwosekar, Kabupaten Malang, Jawa Timur - Sulistyani, Kiki Frida; Irianto , Danang Bimo; Imanda , Yulia Liliyosari (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2024)
Purwosekar village does not have an effective clean water distribution system. Sumber Jenon is located about 3.1km from Purwosekar village, precisely in Gunungronggo village, Tajinan sub-district. Sumber Jenon has potential for continuous water availability throughout the year, from the measurement of instantaneous discharge in getting potential from Sumber Jenon water of 481 liters/det. Tajinan sub-district consists of 12 villages, one of which is Purwosekar village. In 2024 Purwosekar village has a population of 4,786 people, while the projection of 2030 is 5,414 people. The clean water demand taken is 80 l/person/day in accordance with the minimum service standard for rural water. The water demand of the population in Purwosekar Village in 2024 amounted to 6.38 l/dt, in 2030 it amounted to 7.22 l/dt. Pipe network planning is based on water demand in 2030 using epanet 2.0 software. Clean water distribution in Purwosekar Village requires 6,978 meters of pipe, with pipe diameters varying from 2 inches (60mm) to 6 inches (165mm). The pipe used is PVC pipe with a pipe roughness coefficient of Hazen William 120. The length of pipe required for a diameter of 6 inches (165mm) is 1452m, diameter 5 inches (144 mm) 1867m, diameter 4 inches (140mm) 1345m, diameter 3 inches (89 mm) 1281m and diameter 2 inches (60mm) 1033m.